TI_GERICHTE 11.2016.76 vom 8. Februar 2017 , Cancellazione di annotazione nel registro fondiario: spese ripetibili - TI Tribunale d'appello (2017)
Cancellazione di annotazione nel registro fondiario: spese ripetibili